Highly Diastereoselective Construction of Carbon– Heteroatom Quaternary Stereogenic Centers in the Synthesis of Analogs of Bioactive Compounds: From Monofluorinated Epoxyalkylphosphonates to α-Fluoro-, β-, or γ-Amino Alcohol Derivatives of Alkylphosphonates - Rapp, Magdalena; Margas-Musielak, Klaudia; Kaczmarek, Patrycja; Witkowska, Agnieszka; Cytlak, Tomasz; Siodła, Tomasz; Koroniak, Henryk (Frontiers in Chemistry, 2021)
The synthesis of the stable surrogates of an important amino acid (R)-4-amino-3-hydroxybutyric acid (GABOB) such as substituted hydroxy aminophosphonic acids bearing quaternary stereogenic center is presented. Highly diastereoselective formations of fluorinated spiroepoxy alkylphosphonate or related tertiary carbon-containing oxiranes from β-keto phosphonates possessing methyl, phenyl, or cyclohexenyl substituents, are reported. Stereoselective acid-promoted epoxide opening by bromide or azide followed by the reduction/protection afforded tertiary bromides or N-Boc derivatives of β-amino-γ-hydroxy alkylphosphonates in most cases, while the reactions of oxiranes with different amines yielded their β-hydroxy-γ-amino regioisomers. Surprisingly, during the synthesis of amino phosphonic acids, we observe the acid-induced rearrangement proceeded in a high diastereospecific manner, leading finally to substituted β-hydroxy-γ-aminoalkylphosphonic acids.